Government expenditures in Kenya, 1950–2014: Determinants and agricultural growth effects - Benin, Samuel; Odjo, Sunday P. (International Food Policy Research Institute, 2018)
Annual data on Kenya from 1950 to 2014 are used to analyze the determinants of the level and composition of government expenditures and estimate the agricultural-output returns to the different types of government expenditures. The paper analyzes expenditures for six functions (general administration, defense, education, health, agriculture, and other economic functions—transport, communications, etc.) as well as the capital-to-recurrent expenditure ratios within each of the six functions. Simultaneous equations modeling methods are employed, and different diagnostic tests are used to check for and address issues with stationarity, causality, and autocorrelation. Different model specifications are used to assess the sensitivity of the results to using different measures and combinations of the conceptual variables that are hypothesized to affect the composition of government expenditures and agricultural production.